Mobile-to-mobile wireless channels - Zajić, Alenka (Artech House mobile communications series., 2013)
Present-day mobile communications systems can be classified as fixed-to-mobile because they allow mobility on only one end (e.g. the mobile phone to a fixed mobile operator's cell tower). In answer to the consumer demand for better coverage and quality of service, emerging mobile-to-mobile (M-to-M) communications systems allow mobile users or vehicles to directly communicate with each other. This practical book provides a detailed introduction to state-of-the-art M-to-M wireless propagation. Moreover, the book offers professionals guidance for rapid implementation of these communications syste.